Redressing gendered undervaluation in New Zealand aged care: Institutions, activism and coalitions. (September 2020) - Charlesworth, Sara; Heap, Lisa
This article explores the apparent conundrum of how, with minimal employment standards and limited equal pay laws, New Zealand managed to significantly redress the gendered undervaluation of low-paid aged care work. To draw out the pathways to these reforms, we focus on the long-term strategic coalitions that underpinned them. We examine, in particular, the activism of a diverse range of policy actors – unions, employers, industrial and human rights bodies and civil society groups, which together have worked to 'undo' the limitations of equal pay and employment regulation. Our findings point to the benefits of strategic collaboration between policy actors in New Zealand and an approach which recognises the intersection of unequal pay with other gendered dimensions of disadvantage in aged care work. Different strategies used over time by diverse actors helped them overcome inadequate industrial and equal pay infrastructure to realise meaningful increases in hourly rates of pay, buttressed by improved working time arrangements and provision for career progression. We conclude by highlighting some lessons for institutional and policy actors in other national settings drawn from the New Zealand collaborative approach to equal pay in care work.